2018
DOI: 10.1038/s41598-017-17563-z
|View full text |Cite
|
Sign up to set email alerts
|

Grey and white matter volumes either in treatment-naïve or hormone-treated transgender women: a voxel-based morphometry study

Abstract: Many previous magnetic resonance imaging (MRI) studies have documented sex differences in brain morphology, but the patterns of sexual brain differences in transgender women – male sex assigned at birth – with a diagnosis of gender dysphoria (TW) have been rarely investigated to date. We acquired T1-weighted MRI data for the following four (n = 80) groups: treatment-naïve TW (TNTW), TW treated with cross-sex hormones for at least one year (TTW), cisgender men, and cisgender women (cisgender individuals as cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 59 publications
2
37
0
1
Order By: Relevance
“…This result fits with previous longitudinal studies that have shown reductions of cortical thickness in TW pre to post CHT [16]. Structural and functional alterations of the insula have consistently been associated with transgender compared to CG individuals [45,28,29,10,13]. The insula is associated with body and self-perception.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result fits with previous longitudinal studies that have shown reductions of cortical thickness in TW pre to post CHT [16]. Structural and functional alterations of the insula have consistently been associated with transgender compared to CG individuals [45,28,29,10,13]. The insula is associated with body and self-perception.…”
Section: Discussionsupporting
confidence: 90%
“…(1) The classifier trained on healthy CG-participants shows significantly worse performance when applied to a sample of TW (2) The classifier trained on healthy CG-participants performs equally well in a validation sample of CG-patients suffering from major Following our multivariate approach, we used a univariate analysis in two regions of interest that have been associated with brain structural alterations in TW. We investigated local structural brain alterations in the putamen and the insula [28,29,10,13,12,16] corrected for total intracranial volume, age and sexual orientation. Previous results regarding brain structural alterations of TW in the respective regions have been heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…So far, most of the neuroimaging studies in GD have focused on brain sexual dimorphism as a potential etiology for the difference between sex and gender identity. Brain areas such as the insular cortex have been demonstrated to be sexually dimorphic in transgender people, with estradiol and testosterone exerting opposite effects in this area, for instance [13,42]. Moreover, Burke et al [42] found a longitudinal increase in CTh of the left superior temporal gyrus, right superior frontal cortex, and right lateral occipital areas, together with an increase in right insular CTh after CSHT of testosterone administration in transgender men.…”
Section: Discussionmentioning
confidence: 99%
“…Although brain morphology and metabolism seem to become more stable in males and females after puberty, transgender women (transition from male-to-female) undergoing CSHT were reported to present with changes in GMV [12,13]. Furthermore, CSHT was associated to bilateral CTh changes in both transgender men (femaleto-male transitioning) and transgender women [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This, a subject studied purely in gender dysphoria, has shown the existence of morphological alterations of the insula cortex (IC), probably related to the discrepancy between physical image and mental perception of one's body (Spizzirri et al, 2018). IC is also part of the coding of emotional and social aspects, representing a potential reason for the development of anxiety and relational pathologies (Gogolla, 2017).…”
Section: Dear Editormentioning
confidence: 99%